Penerapan Fungsi Sosial Terhadap Hak Kekayaan Intelektual Di Dalam Masyarakat - Chandra Yusuf; Nelly Ulfah Anisariza (Faculty of Law, Andalas University, 2019)
This article analyzes the position of ideal social functions in IPR which should be regulated by the government. The purpose of writing this article is to examine the social functions of the government to overcome the conflicting intellectual property rights of individuals with the rights of other individuals. This article proves that IPR aims to protect individual intellectual property. The application of IPR has separated intellectual property from the people. Though intellectual property arises in the community. The community environment can provide inspiration to find ideas. Individuals cannot live outside the community. Therefore, intellectual property must provide benefits to the community. Social functions will play a role in overcoming conflicts of intellectual property rights between owners. The dialectic pendulum that sways between the two points of view will stop and produce the most ideal position. In accordance with the dialectic of Hegel which places the initial position (thesis) which has a circle within itself. The negation that occurs makes the change to the final position (anti-thesis), which results in the most recent position (synthesis). If individual discoveries are absolute rights, then other individuals also have the same rights. IPR will be bound in its use in the community. If an individual's intellectual property rights conflict with the rights of other individuals, the government will emphasize social functions in overcoming them.